Between past and future of Latin America: Lessons from Brazil, Chile, Costa Rica and the Dominican Republic - Eliana Cardoso (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
This paper provides a synthesis of the four papers on the Latin American and Caribbean economies: Brazil, Chile, Costa Rica, and the Dominican Republic. It focuses on the following themes: macroeconomic stabilization and fiscal challenges, poverty and inequality, and the use of natural resources to create growth. The paper then draws lessons for development.
Keywords: N86; O1; O38; 330; macroeconomic growth; fiscal challenges; resource-rich countries; Latin America and the Caribbean